Strategi Penerjemahan Menu Makanan Restoran dalam Menarik Wisatawan Asing: Analisis Linguistik - Kadek Ayu Ekasani; Ida Ayu Gayatri Kesumayathi (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Restaurant menu translation plays a vital role in attracting international tourists and expanding the culinary market of a region. This study aims to analyze restaurant menu translation strategies using a descriptive qualitative approach. Data were collected through observation, interviews, and document analysis of translated menus. The findings indicate that description, adaptation, and amplification are the most commonly used strategies to improve the readability and appeal of menus in the target language. These strategies help bridge linguistic and cultural differences, making it easier for tourists to understand the content of the menu. However, translation errors were still found and may lead to misunderstandings and decrease the attractiveness of certain dishes.In addition to qualitative analysis, a survey was conducted involving 50 foreign tourists in tourist areas to gain insight into their perceptions of menu translations. The survey results revealed that 80% of respondents found the menu translations clear, although 20% still encountered confusion with some terms. Moreover, 75% stated that appealing menu descriptions increased their interest in trying local dishes. Regarding language preferences, 60% of respondents preferred menus that included original dish names with English descriptions, while 40% favored full English translations. Some tourists also suggested including more detailed information, such as spiciness levels and main ingredients.Overall, effective menu translation not only enhances the culinary experience of tourists but also strengthens a restaurant's competitiveness and supports the promotion of local cuisine in the global market.